Performance Analysis of Regional Revenue and Expenditure Budget Management in Medan City Government for Fiscal Year 2019-2023 - Bintang, Nopa Rohmendena; Purba, Sonia Helena; Panjaitan, Sulastri Destriani; Simanjuntak, Syaloom Lestari; Chrisna, Heriyati (Lembaga Riset Mutiara Akbar, 2024)
This study aims to analyze the Performance of Regional Revenue and Expenditure Budget Management in the Medan City Government for the 2019 to 2023 budget years which can be seen from the analysis of revenue performance and expenditure performance analysis. This study is descriptive with a quantitative approach using secondary data, namely from the Medan City Regional Revenue and Expenditure Budget Realization Report from 2019 to 2023 obtained from the official website of the Medan City Government. The results of this study indicate that the financial performance of Medan City is seen from the analysis of income which shows an average of 86.2% which is categorized as quite effective, the analysis of expenditure which shows an average of 78.5% is included in the less effective category, the analysis of income growth with an average of 3.7% is categorized as very low, the analysis of expenditure growth with an average of 5.8% is categorized as very low, the financial independence ratio with an average of 38.3% is categorized as sufficient, the tax effectiveness ratio with an average of 64.8% is categorized as quite effective, the analysis of expenditure harmony is categorized with an average of 18.4% mode expenditure, 73.7% operational expenditure and the analysis of expenditure efficiency with an average of 78.1% is categorized as efficient.